2008
DOI: 10.1177/0146167207312312
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Interpersonal Complementarity Within Roommate Dyads

Abstract: Complementarity theory proposes specific hypotheses regarding interpersonal styles that will result in successful relationships. The present study sought to extend previous research on gender differences in complementarity through the examination of same-sex peer dyads and the use of informant reports of interpersonal style. One hundred twenty participants (30 male and 30 female roommate dyads) completed interpersonal circumplex ratings of their roommates and a relationship cohesion measure. Examinations of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…Hill, Rubin, and Peplau (1976) found that similarity in age, physical attractiveness, educational aspirations, and intelligence are positively related to relationship stability. At the same time, Ansell, Kurtz, and Markey (2008) found that similarity on warmth and complementarity on dominance predicts cohesion among same-sex college roommates. The evidence for similarity effects is wider and stronger than the evidence for complementarity effects, but both reflect emergent properties of the relationship.…”
Section: Relationship-level Predictorsmentioning
confidence: 90%
“…Hill, Rubin, and Peplau (1976) found that similarity in age, physical attractiveness, educational aspirations, and intelligence are positively related to relationship stability. At the same time, Ansell, Kurtz, and Markey (2008) found that similarity on warmth and complementarity on dominance predicts cohesion among same-sex college roommates. The evidence for similarity effects is wider and stronger than the evidence for complementarity effects, but both reflect emergent properties of the relationship.…”
Section: Relationship-level Predictorsmentioning
confidence: 90%
“…First, the coaches in our sample do not necessarily represent the large variety of professional coaches in the field (e.g., in terms of gender, age, experience, cultural background, and coaching approach). As our sample included predominantly female coaches and clients, the data did not allow for analyzing gender effects, although previous research suggests gender differences in interpersonal dissimilarity (Ansell et al 2008). As the dominance and affiliation values of the male coach did not differ substantially from female coach values, we did not exclude the corresponding dyad from our analysis.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Kurtz and colleagues suggest that roommate pairs are ideal for research into interpersonal relationships because they occur in a natural and unstructured setting, but allow experimental control when students are randomly assigned to rooms and ratings are collected at specific intervals following their acquaintance. These circumstances provide researchers with a unique opportunity to study newly formed same sex peer dyads interacting across situations and over time (Ansell et al, 2008;Kurtz & Sherker, 2003;Markey & Kurtz , 2006). In addition to the work on interpersonal relationships between roommates by Kurtz and Sherker, others have used roommate pairs to evaluate the relationship between trait ambiguity and self-peer agreement in personality judgment (i.e.…”
Section: Importance Of Longitudinally Studying New Relationshipsmentioning
confidence: 99%